Identification and quantification of major carotenoids of deep yellow-fleshed yam (tropical Dioscorea dumetorum - Ferede, R.; Maziya-Dixon, B.B.; Alamu, O.E.; Asiedu, Robert (2010)
Vitamin A deficiency (VAD) is prevalent in most developing countries. Increasing provitamin A carotenoid content in staple crops such as yam, maize and cassava can minimize this deficiency. Yam (Dioscorea species) is a major staple food in many tropical and subtropical countries. Despite its wide consumption, there is limited information on the type and amount of carotenoids in different species. This study was conducted to update methods for extraction of carotenoids, to identify and quantify the major carotenoids and determine the provitamin A (PVA) content in Dioscorea dumetorum (trifoliate yam). The carotenoid components of Dioscorea dumetorum were extracted using solvent extraction, and major components were separated by high-performance liquid chromatography (HPLC) and identified by their UV/visible absorption spectral data and co-elution with reference standards using HPLC, Thin Layer Chromatography (TLC) and Open Column Chromatography (OCC). Results obtained indicate that the major carotenoids in the deep yellow fleshed trifoliate yam are trans-β-carotene-5,8-epoxide 9.4±3.9 μg g-1 (55.1% ), β-cryptoxanthin-5,6-epoxide 4.7±1.2 μg g-1 (27.0%), β-carotene-5,6-epoxide 1.7±0.07 μg g-1 (9.6%) and cis and trans β-carotene 1.2±0.4 μg g-1 (7.3%). Provitamin A content was calculated and the average provitamin A carotenoid in the deep yellow-fleshed genotypes was 8.9±3.2 μg g-1 representing 52% of the total carotenoid content. The profile of carotenoids and the high concentration of trans-β-carotene-5,8-epoxide found in the deep yellow-fleshed D. dumetorum are unique compared to other species of yam or other tuber roots such as cassava and sweet potato.